2014
DOI: 10.1007/s12149-014-0810-4
|View full text |Cite
|
Sign up to set email alerts
|

First experience with early dynamic 18F-NaF-PET/CT in patients with chronic osteomyelitis

Abstract: This pilot study suggests that, in patients with COM, ed(18)F-NaF -PET offers additional information about early radiotracer distribution to standard (18)F-NaF -PET/CT, similar to a three-phase bone scan. The results should be validated in larger trials which directly compare ed(18)F-NaF-PET to a three-phase bone scan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 17 publications
1
31
0
1
Order By: Relevance
“…In line with the non-quantitative studies mentioned in the introduction, i.e. [4, 5, 7, 9, 10], we found increased blood perfusion in the OM lesions (Table 3), as well as in the ST lesions (Table 4). However, as hypothesized, we found a quite clear distinction between the OM lesions and the ST lesions as the increase was significantly higher in the infected soft tissues than in the osteomyelitic lesions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with the non-quantitative studies mentioned in the introduction, i.e. [4, 5, 7, 9, 10], we found increased blood perfusion in the OM lesions (Table 3), as well as in the ST lesions (Table 4). However, as hypothesized, we found a quite clear distinction between the OM lesions and the ST lesions as the increase was significantly higher in the infected soft tissues than in the osteomyelitic lesions.…”
Section: Discussionsupporting
confidence: 91%
“…The study did not report quantitative perfusion, though, but found PET/CT valuable as a tool in the assessment. Two recent papers describe experiences with dynamic PET/CT, using [ 18 F]NaF [9] or [ 18 F]FDG [10] as tracer; both studies reported increased standardized uptake values (SUV) in the volume of interest (VOI) positioned at the site of chronic OM infection.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the radionuclide angiographic and blood pool phase images of a traditional 99m Tc-MDP three-phase bone scintigraphic examination are not routinely possible with 18 F-NaF PET/CT because standard images can be acquired 90 minutes after injection. However, 18 F-NaF PET/CT has emerging potential to become a substitute for two-phase bone scintigraphy in the identification of bone inflammation (25). Depending on the type of PET scanner used, 18 F-NaF PET/CT could be performed similarly to a three-phase bone scintigraphic examination by obtaining a short dynamic acquisition within the first 10 minutes after the injection.…”
Section: Comparison Of 18 F-naf and 99m Tc-mdp As Bone Agentsmentioning
confidence: 99%
“…Depending on the type of PET scanner used, 18 F-NaF PET/CT could be performed similarly to a three-phase bone scintigraphic examination by obtaining a short dynamic acquisition within the first 10 minutes after the injection. This acquisition could conceivably represent the angiographic and blood pool phases of threephase bone scintigraphy (25,26). The utility of such an approach has not been thoroughly investigated, and prospective studies are needed before its incorporation into routine clinical practice.…”
Section: Comparison Of 18 F-naf and 99m Tc-mdp As Bone Agentsmentioning
confidence: 99%
“…A recent study shows the NaF18 PET imaging modality is of higher resolution than PET. NaF18 PET images have higher sensitivity than bone scan for identifying osseous metastasis, but this technique is not available clinically [20].…”
Section: Discussionmentioning
confidence: 99%